Radiation Response of Cultured Human Cells Is Unaffected by Johrei. Issue 2 (2007) - Hall, Zach; Luu, Tri; Moore, Dan; Yount, Garret
Abstract : Johrei has been credited with healing thousands from radiation wounds after the Hiroshima and Nagasaki bombs in 1945. This alternative medical therapy is becoming increasingly popular in the United States, as are other Energy Medicine modalities that purport to influence a universal healing energy. Human brain cells were cultured and exposed to increasing doses of ionizing radiation. Experienced Johrei practitioners directed healing intentionality toward the cells for 30 min from a distance of 20 cm and the fate of the cells was observed by computerized time-lapse microscopy. Cell death and cell divisions were tallied every 30 min before, during and after Johrei treatment for a total of 22.5 h. An equal number of control experiments were conducted in which cells were irradiated but did not receive Johrei treatment. Samples were assigned to treatment conditions randomly and data analysis was conducted in a blinded fashion. Radiation exposure decreased the rate of cell division (cell cycle arrest) in a dose-dependent manner. Division rates were estimated for each 30 min and averaged over 8 independent experiments (4 control and 4 with Johrei treatment) for each of 4 doses of X-rays (0, 2, 4 and 8 Gy). Because few cell deaths were observed, pooled data from the entire observation period were used to estimate death rates. Analysis of variance did not reveal any significant differences on division rate or death rate between treatment groups. Only radiation dose was statistically significant. We found no indication that the radiation response of cultured cells is affected by Johrei treatment.